2022
DOI: 10.1177/17534666221075493
|View full text |Cite
|
Sign up to set email alerts
|

Digital healthcare in COPD management: a narrative review on the advantages, pitfalls, and need for further research

Abstract: Chronic obstructive pulmonary disease (COPD) remains a leading cause of morbidity and mortality despite current treatment strategies which focus on smoking cessation, pulmonary rehabilitation, and symptomatic relief. A focus of COPD care is to encourage self-management, particularly during COVID-19, where much face-to-face care has been reduced or ceased. Digital health solutions may offer affordable and scalable solutions to support COPD patient education and self-management, such solutions could improve clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 164 publications
0
24
0
Order By: Relevance
“…Cigarette smoking is the main cause of COPD [ 75 ], and it is known to cause inflammation and oxidative stress which, together, play fundamental roles in the pathogenesis of chronic inflammatory diseases such as COPD [ 76 , 77 ]. Current treatment strategies for COPD involve pulmonary rehabilitation, smoke cessation, and pharmacological relief of symptoms through inhalational therapy [ 78 ]. Despite this, COPD still represents a leading cause of morbidity and mortality worldwide [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is the main cause of COPD [ 75 ], and it is known to cause inflammation and oxidative stress which, together, play fundamental roles in the pathogenesis of chronic inflammatory diseases such as COPD [ 76 , 77 ]. Current treatment strategies for COPD involve pulmonary rehabilitation, smoke cessation, and pharmacological relief of symptoms through inhalational therapy [ 78 ]. Despite this, COPD still represents a leading cause of morbidity and mortality worldwide [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face assessment of mothers and providing access to a phone receptionist who can facilitate personal assistance when needed were examples raised by mothers and stakeholders to help mothers who might lack the competencies to navigate the digital health care system. An integrative approach to the implementation of digital interventions should be built into the service to ensure accessibility and inclusivity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it was related to whether patients did or did not have a computer at home or whether their computer skills were (perceived to be) too low. Several studies in the systematic review authored by Koivunen and Saranto [60] and other studies of various chronic diseases, including COPD [65][66][67], have highlighted that lack of access and skills are obstacles to using eHealth tools among patients. For example, we recently found that among patients with COPD enrolled in primary care, about 40% of eligible patients with COPD declined participation in an eHealth intervention due to no/limited experience with computers [17].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Participants also had high knowledge of how to use the internet, with 91% having used the internet during the last 3 months and 85% almost every day. Taken together, indicating that although low access and computer skills are obstacles to using eHealth tools across various patient groups [65][66][67], it is vital that health care professionals do not draw firm conclusions based on their perception of the computer skills of their patients. Instead, a more relevant alternative for health care professionals would be to assess the level of health literacy among their patients to aid them in deciding whether the incorporation of an eHealth tool would be feasible.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%